2009
DOI: 10.1177/1098300709340700
|View full text |Cite
|
Sign up to set email alerts
|

Turkish Special Education Teachers’ Reported Use of Positive and Reductive Interventions for Problem Behaviors: An Examination of the Variables Associated With Use

Abstract: The purpose of this survey study was to determine the following: (a) What strategies do Turkish special education teachers use to address problem behaviors in their classroom? (b) What are teachers' views with regard to the effectiveness and acceptability of these strategies? (c) Is there a relationship between the use of strategies and teachers' perceived effectiveness and acceptability? and (d) Are differences among teacher ratings of strategy use, effectiveness, and acceptability associated with teacher cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(53 reference statements)
1
1
0
Order By: Relevance
“…The present findings were also consistent with previous acceptability research with respect to interventions for challenging behaviours -researchers found that acceptability varied as a function of the type of intervention (e.g. Kazdin, 1980aKazdin, , 1980bTuran et al, 2010). Follow-up interviews provided further insights about teachers' LIRP ratings.…”
Section: Type Of Intervention Approachsupporting
confidence: 90%
See 1 more Smart Citation
“…The present findings were also consistent with previous acceptability research with respect to interventions for challenging behaviours -researchers found that acceptability varied as a function of the type of intervention (e.g. Kazdin, 1980aKazdin, , 1980bTuran et al, 2010). Follow-up interviews provided further insights about teachers' LIRP ratings.…”
Section: Type Of Intervention Approachsupporting
confidence: 90%
“…However, most of the research in this area is restricted to acceptability information pertaining to interventions designed to address challenging behaviour (e.g. Kazdin, 1980a;Turan, Erbas, Ozkan, & Kurkcuoglu, 2010;Witt & Martens, 1983). In the area of language interventions, information on treatment acceptability predominantly relies on consumer satisfaction measures (e.g.…”
mentioning
confidence: 99%